2020
DOI: 10.14293/s2199-1006.1.sor-.pplypgg.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Students Mathematics Interest as Correlate of Achievement in Mathematics: Evidence from a Sub-Saharan Student Sample

Abstract: This study was carried out to investigate Mathematics interest as a correlate of Basic 9 students achievement in Mathematics in Gboko Metropolis, Benue State, Nigeria. Three research questions were asked and three hypotheses were formulated. The study adopted a correlation design. The population of the study was 3,682 while a sample of 400 Basic 9 students was drawn from ten secondary schools using multistage sampling procedure made up of 200 male and 200 female students. Two research instruments Maths Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Oluyemo et al (2020) discovered that compared to their male counterparts, females show less interest in mathematics. Studies on gender differences in mathematics support the literature; for instance, Oluyemo et al (2020) in Nigeria and Tembe et al (2020) in the Sub-Saharan region both discovered that females exhibited much lower interest than boys. However, Song et al (2019) discovered that there were no differences between girls' and boys' mean interests, and Musbahu et al (2020), in a study about Junior secondary schools in Nigeria, discovered that female students showed greater interest in mathematics than their male counterparts.…”
Section: Levels and Differences In Mathematics Interestmentioning
confidence: 85%
“…Oluyemo et al (2020) discovered that compared to their male counterparts, females show less interest in mathematics. Studies on gender differences in mathematics support the literature; for instance, Oluyemo et al (2020) in Nigeria and Tembe et al (2020) in the Sub-Saharan region both discovered that females exhibited much lower interest than boys. However, Song et al (2019) discovered that there were no differences between girls' and boys' mean interests, and Musbahu et al (2020), in a study about Junior secondary schools in Nigeria, discovered that female students showed greater interest in mathematics than their male counterparts.…”
Section: Levels and Differences In Mathematics Interestmentioning
confidence: 85%